2016
DOI: 10.1177/1534735416639714
|View full text |Cite
|
Sign up to set email alerts
|

Survival Analysis of Advanced Non–Small Cell Lung Cancer Patients Treated by Using Wheel Balance Cancer Therapy

Abstract: Objective. To investigate the clinical effect and the overall survival (OS) rate of patients with advanced non–small cell lung cancer (NSCLC) who have undergone Wheel Balance Cancer Therapy (WBCT). Methods. The cases of 33 patients with advanced NSCLC who were treated with WBCT at the East West Cancer Center (EWCC) between October 4, 2004, and October 3, 2013, without undergoing concurrent conventional treatment were analyzed. The Kaplan-Meier method was used to estimate the OS of the cases, and the median OS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…It is possible that patients treated with Ct first showed a better prognosis relative to patients who received EGFR-TKIs first because the Ct first group may have had better PS than the EGFR-TKI first group. Several studies have reported that good PS at the time of first-line treatment affects OS (19). The present study was based on medical records of the Tokyo Medical University Hospital, but there were many cases in which the PS was not stated clearly.…”
Section: Discussionmentioning
confidence: 97%
“…It is possible that patients treated with Ct first showed a better prognosis relative to patients who received EGFR-TKIs first because the Ct first group may have had better PS than the EGFR-TKI first group. Several studies have reported that good PS at the time of first-line treatment affects OS (19). The present study was based on medical records of the Tokyo Medical University Hospital, but there were many cases in which the PS was not stated clearly.…”
Section: Discussionmentioning
confidence: 97%
“…WBCT consists of herbal medications, acupuncture, moxibustion, heat therapy for activating metabolism, exercise, an anticancer diet, and meditation. [9,10] Although other treatments lean toward managing symptoms and improving the immune system, the 3 treatments of WBCT the multiherbal formula containing Panax notoginseng Radix , Cordyceps militaris , P ginseng C.A.Mey. , and Boswellia carterii BIRDWOOD (HangAmDan-B1; HAD-B), the herbal formula containing Rhus verniciflua Stoke (Geonchil-jung), and (3) cultivated wild ginseng pharmacopuncture, are prescribed primarily for their anticancer effects.…”
Section: Methodsmentioning
confidence: 99%
“…By maximizing patients’ natural healing powers, WBCT, either combined with western therapies or administered as a sole therapy, has been reported to have the benefits of decreasing side effects associated with CCT, increasing quality of life, and preventing metastasis. [9,10]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 8 ] Our integrative cancer center has implemented anticancer TKM treatment (ACTKMT) as an integrative holistic cancer care for the past 20 years and has reported its benefits of reducing side effects associated with conventional cancer therapy, improving quality of life, and preventing metastasis. [ 9 , 10 ] However, this cancer treatment modality has not been studied through prospective survival analysis in terms of clinical impact by its key component.…”
Section: Introductionmentioning
confidence: 99%